2018
DOI: 10.1137/16m105589x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Techniques for Scheduling on a Machine with Varying Speed

Abstract: We study scheduling problems on a machine with varying speed. Assuming a known speed function we ask for a cost-efficient scheduling solution. Our main result is a PTAS for minimizing the total weighted completion time in this setting. This also implies a PTAS for the closely related problem of scheduling to minimize generalized global cost functions. The key to our results is a re-interpretation of the problem within the wellknown two-dimensional Gantt chart: instead of the standard approach of scheduling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 37 publications
(62 reference statements)
0
47
0
Order By: Relevance
“…Further, the area of scheduling with generalized non-decreasing (completion-) time dependent cost functions, such as minimizing j w j f (C j ), e.g. Epstein et al (2012), Megow and Verschae (2018), Höhn and Jacobs (2015), or even more general job-individual cost functions j f j (C j ), e.g. Bansal and Pruhs (2014), Höhn et al (2018), Cheung and Shmoys (2011), Cheung et al (2017) has received quite some attention.…”
Section: Related Workmentioning
confidence: 99%
“…Further, the area of scheduling with generalized non-decreasing (completion-) time dependent cost functions, such as minimizing j w j f (C j ), e.g. Epstein et al (2012), Megow and Verschae (2018), Höhn and Jacobs (2015), or even more general job-individual cost functions j f j (C j ), e.g. Bansal and Pruhs (2014), Höhn et al (2018), Cheung and Shmoys (2011), Cheung et al (2017) has received quite some attention.…”
Section: Related Workmentioning
confidence: 99%
“…This is in contrast to the fact that the classic knapsack problem and its covering version admit pseudo-polynomial time algorithms. Megow and Verschae [17] gave a PTAS for the covering version of KPSC.…”
Section: Related Studiesmentioning
confidence: 99%
“…We refer the reader to a number of excellent surveys [3,12] and to the references therein for a more comprehensive literature review. That said, a particularly relevant work is that of Megow and Verschae [14], who developed a PTAS for the generalized objective of minimizing n j=1 v j f (C j ), where f is an arbitrary non-decreasing cost function. Later on, Höhn [12] observed that any instance of the airplane refueling problem can be rephrased in terms of this minimization problem by replacing the term 1/C j in the objective function with 1 − 1/C j .…”
Section: Related Workmentioning
confidence: 99%